Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1007/bf01833635
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of moles (Talpa europaea L.) in relation to physical habitat and food supply

Abstract: The distribution and population density of the mole (Talpa europaea L.) and its main food item, earthworms (Lumbricidae) were determined in relation to physical habitat factors in an upland pasture in southeast Scotland. The results showed that the species distribution and the abundance of earthworms were related to the physical habitat. Moles lived in the areas where earthworms were more abundant, and fewer moles were found in the areas with few earthworms. The distribution of moles was not related to the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…In these previous papers, habitat suitability was principally judged by the presence or absence of moles. Funmilayo (1977) compared mole densities on two fields and attempted to relate the differences to a few soil characters. The study reported here seems to be the first in which habitat relationship of moles were deduced from quantified variables in a comprehensive manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these previous papers, habitat suitability was principally judged by the presence or absence of moles. Funmilayo (1977) compared mole densities on two fields and attempted to relate the differences to a few soil characters. The study reported here seems to be the first in which habitat relationship of moles were deduced from quantified variables in a comprehensive manner.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of these moles, as indicated by the number of hills made in a given areas, has been related to the bulk density of the soil. Skoczen (1958) and Funmilayo (1977) maintain that most hills occur were the soil is dense, but Arlton (1936) stated that most hills are in light soil. Funmilayo (1977) further found that there were more earthworms in a field with many molehills than in another field with fewer hills.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The specimens came from the following institutions: the American Museum of Natural History (New York, USA), the Smithsonian Institution (Washington D.C., USA), the Data on climatic parameters were collected based upon the biology of the species. Like all insectivores, moles have a high metabolic rate, and their activity patterns and territorial behaviour are mainly related to the availability of prey, mostly earthworms (Skoczen, 1966;Funmilayo, 1977, Gorman & Stone, 1990Loy, 1992), whose density is related to the humidity of soils (Bouche, 1987;Cuendet, 1987). Humidity can also affect hardness of soil and therefore has an influence on digging (Gorman & Stone, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…However, more general patterns of earthworm consumption may result from gradients in climatic humidity, as in the case of the eastern European population of the Badger Meles meles (Goszczy nski et al 2000), or altitude, as in populations of several species of invertebratefeeding birds breeding in Scotland (Pearce-Higgins 2010). In turn, a classic case of a strong local relationship between earthworms and their predators is that of European Moles Talpa europaea, the abundance of which is higher at sites with a greater density of earthworms (Skocze n 1966, Funmilayo 1977. Similarly, at higher local densities, earthworms may become a staple dietary item of a variety of opportunistic feeders.…”
mentioning
confidence: 99%